2019
DOI: 10.1111/pce.13513
|View full text |Cite
|
Sign up to set email alerts
|

Plant hormone effects on isoprene emission from tropical tree in Ficus septica

Abstract: Plant hormones and the circadian rhythm have been implicated in coordinated control of isoprene emission in plants. To gain insights into the signalling networks, foliar application of plant hormones was conducted in a native emitter, Ficus septica.Spraying of 50 μM jasmonic acid (JA) gradually decreased isoprene emission by 88% compared with initial levels within 5 days, and emission increased after relief from JA application. We further explored the molecular regulatory mechanism of isoprene emission by anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Although high rates of isoprene emission are found in some monocot species such as Arundo donax and Phragmites australis , only recently was a monocot isoprene synthase cloned (Li et al, ). Analysis of the ISPS promoter of Ficus septica revealed the presence of cis‐elements for MYC2 (jasmonic acid‐JA signalling) and LHY (a circadian clock protein), which shows that isoprene synthesis can be regulated through modulation of ISPS by hormones and circadian rhythms (Parveen et al, ).…”
Section: Biochemical Control Of Isoprene Emissionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although high rates of isoprene emission are found in some monocot species such as Arundo donax and Phragmites australis , only recently was a monocot isoprene synthase cloned (Li et al, ). Analysis of the ISPS promoter of Ficus septica revealed the presence of cis‐elements for MYC2 (jasmonic acid‐JA signalling) and LHY (a circadian clock protein), which shows that isoprene synthesis can be regulated through modulation of ISPS by hormones and circadian rhythms (Parveen et al, ).…”
Section: Biochemical Control Of Isoprene Emissionmentioning
confidence: 99%
“…Mechanostimulation and wounding of Medicago truncatula led to an increase in transcription of the JA biosynthesis gene 1‐aminocyclopropane‐1‐carboxylate oxidase 2 ( ACO2 ) and 1‐deoxy‐ d ‐xylulose 5‐phosphate synthase 2 ( DXS2‐1 ) of the MEP pathway, with subsequent increases in JA biosynthesis (Tretner, Huth, & Hause, ). Recently, Parveen et al () showed that application of JA to Ficus septica reduces ISPS expression, protein content, and isoprene emission whereas DXS is increased. Analysis of ISPS promoter regions revealed the presence of cis‐elements that can be targeted by transcription factors to alter gene expression in response to JA (Parveen et al, ).…”
Section: Physiological Roles Of Isoprene In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors hypothesize that the interaction between JA and auxin modulates IspS gene expression via the transcription factor MYC2 (Parveen et al . 2019). However, MYC2 only explained 27% of the total variation in IspS expression, suggesting the occurrence of an additional transcription factor or intermediate signal transducer to control IspS (Fig.…”
Section: Discussionmentioning
confidence: 99%